1998
DOI: 10.1046/j.1365-2222.1998.00302.x
|View full text |Cite
|
Sign up to set email alerts
|

Airborne house dust particles and diesel exhaust particles as allergen carriers

Abstract: Soot particles in airborne house dust may act as carriers of several allergens in indoor air. Furthermore, DEP has the ability to bind all the four allergens investigated under aqueous conditions in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 33 publications
1
63
1
Order By: Relevance
“…PM10 presented a positive trend relationship especially with Aspergillus and Alternaria (Adhikari et al, 2006). PM10 can affect the morphology, allergenicity and aerodynamic attributes of bioaerosols (Adhikari et al, 2006, Ormstad et al, 1998. However, Lin & Li (2000) and Sousa et al, (2008) concluded that there is a non-significant positive correlation between PM10 and Aspergillus or…”
Section: Air Pollutionmentioning
confidence: 85%
“…PM10 presented a positive trend relationship especially with Aspergillus and Alternaria (Adhikari et al, 2006). PM10 can affect the morphology, allergenicity and aerodynamic attributes of bioaerosols (Adhikari et al, 2006, Ormstad et al, 1998. However, Lin & Li (2000) and Sousa et al, (2008) concluded that there is a non-significant positive correlation between PM10 and Aspergillus or…”
Section: Air Pollutionmentioning
confidence: 85%
“…Furthermore, a decrease in IFN-γ expression induced by allergen plus DEP injection had also been reported (37). DEP could have the ability to bind allergen and act as carriers of several allergens (38). These findings suggest that DEP have potencies not only to induce airway inflammation by themselves but also to augment the efficacy of antigen presentation (39) by acting as carriers.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, we demonstrated that the same levels of macrophages containing MWCNT in both MWCNT and MWCNT+ antigen groups were observed. In addition, the amount of allergen carried on the particles is dependent on the particle surface area 32) and MWCNT share particle characteristics, such as a nano-sized diameter and a large surface area, with ultrafine particles of urban air pollution, 33) suggesting that the large particle surface area of MWCNT is likely to augment the carried amount of allergen and thus the cellular response.…”
Section: Discussionmentioning
confidence: 99%